Bloqueio dos receptores 5-HT2 da substância cinzenta periaquedutal suprime o efeito ansiolítico resultante do antagonismo dos receptores 5-HT1A do núcleo mediano da rafe em camundongos - Souza, Vanessa Nunes de (Universidade Federal de São Carlos, 2011)
Several lines of evidence support the involvement of serotonergic (5-HT) neurons of the median raphe nucleus (MRN) in anxiety-like behaviour. In this context, it is known that blockade of 5- HT1A somatodendritic autoreceptors in the midbrain raphe nuclei increases the firing rate of these neurons, disinhibiting 5-HT release in postsynaptic target areas such as amygdala, hippocampus and periaqueductal grey matter (PAG). However, while activation of 5-HT1A or 5- HT2 receptors in forebrain targets such as the amygdala or hippocampus enhances anxiety-like behaviours in rodents, stimulation of both receptor subtypes in the midbrain PAG markedly reduces anxiety-like behaviour. In view of these findings, the present study investigated whether the anti-anxiety effects induced by pharmacological disinhibition of 5-HT neurons in the MRN are attenuated by the blockade of 5-HT2 receptors within the PAG. Mice received combined intra-PAG injection with ketanserin (10 nmol/0.1 μl), a 5-HT2 receptor antagonist, followed by intra-MRN injection of WAY-100635 (5.6 nmol/0.l μl), a highly selective 5-HT1A receptor antagonist. They were then individually exposed to the elevated plus-maze (EPM), with the videotaped behavioural sessions subsequently scored for both conventional and ethological measures. The results confirmed that intra-MRN infusion of WAY100635 (5.6 nmol/0.l μl)reduces behavioural indices of anxiety without significantly altering general activity measures, and further showed that this effect was completely blocked by intra-PAG pretreatment with an intrinsically-inactive dose of ketanserin (10 nmol/0.1 μl). Together, these results suggest that 5HT2 receptor populations located within the midbrain PAG play a significant role in the reduction of anxiety observed following disinhibition of 5-HT neurons in the MRN.
Blockade of 5-HT2 receptors in the periaqueductal grey matter (PAG) abolishes the anxiolytic-like effect of 5-HT1A receptor antagonism in the median raphé nucleus in mice 2011
Keywords: Ansiedade; Labirinto em cruz elevado; 5-HT2; Substância cinzenta periaquedutal; Camundongo; CIENCIAS BIOLOGICAS::FISIOLOGIA